An Embodied Cognition Perspective on the Role of Interoception in the Development of the Minimal Self - Musculus, Lisa; Tünte, Markus R.; Raab, Markus; Kayhan, Ezgi (Frontiers in Psychology, 2021)
Interoception is an often neglected but crucial aspect of the human minimal self. In this perspective, we extend the embodiment account of interoceptive inference to explain the development of the bodily, minimal self in humans. To do so, we first provide a comparative overview of the central accounts addressing the link between interoception and the bodily, minimal self. Grounding our arguments on the embodiment framework, we propose a bidirectional relationship between motor and interoceptive states, which jointly contribute to the development of minimal self. We present empirical findings on interoception in development and discuss the role of interoception in the development of minimal self. Moreover, we make theoretical predictions that can be tested in future experiments. Our goal is to provide a comprehensive view on the mechanisms underlying bodily, minimal self by explaining the role of interoception in the development of minimal self.